2022
DOI: 10.3390/antiox11081594
|View full text |Cite
|
Sign up to set email alerts
|

H2O2 and Ca2+ Signaling Crosstalk Counteracts ABA to Induce Seed Germination

Abstract: Seed germination is a critical stage and the first step in the plant’s life cycle. H2O2 and Ca2+ act as important signal molecules in regulating plant growth and development and in providing defense against numerous stresses; however, their crosstalk in modulating seed germination remains largely unaddressed. In the current study, we report that H2O2 and Ca2+ counteracted abscisic acid (ABA) to induce seed germination in melon and Arabidopsis by modulating ABA and gibberellic acid (GA3) balance. H2O2 treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 57 publications
1
3
0
Order By: Relevance
“…This is roughly consistent with our findings in this study (Fig. 7 d), indicating that ZmPMP3g overexpression can harmonize the ABA-GA1-GA3 (especially GA1) balance, somewhat different from the homeostasis of ABA-GA3 in melon ( Cucumis melo ) seeds under treatments with exogenous ABA 45 and ABA-GA3-GA4 (especially GA4) during early growth stage of cucumber ( C. sativus ) treated by melatonin under salt 43 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This is roughly consistent with our findings in this study (Fig. 7 d), indicating that ZmPMP3g overexpression can harmonize the ABA-GA1-GA3 (especially GA1) balance, somewhat different from the homeostasis of ABA-GA3 in melon ( Cucumis melo ) seeds under treatments with exogenous ABA 45 and ABA-GA3-GA4 (especially GA4) during early growth stage of cucumber ( C. sativus ) treated by melatonin under salt 43 .…”
Section: Discussionsupporting
confidence: 91%
“…DELLA degradation is also involved in COP1, FKF1/F-box, skp1, CUL1, and F-box proteins 38 . However, accumulating evidence shows that GA and ABA exert an antagonistic effect and need a balance/homeostasis in plants 39 42 , high GA and low ABA levels under favorable conditions and the reverse ratio under unfavorable conditions 43 45 . This is roughly consistent with our findings in this study (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This critical developmental step is regulated by diverse endogenous and exogenous factors [17]. Previous results reveal that seed germination is positively regulated by some novel singling molecules, such as H 2 S [18], H 2 O 2 [19], Ga 2+ [19], ABA [19], NO [20], and CO [21]. Additionally, an increasing number of studies have recently reported that plant hormones promote seed germination, such as ABA, auxin, ET, GA, CK, JA, and BRs [22].…”
Section: Introductionmentioning
confidence: 99%
“…Seed aging represents an irreversible process characterized by the gradual decline of seed vigor, including reduction in antioxidant systems, disruption of cellular membranes, genetic integrity damage, lipid peroxidation, and protein degradation [ 29 , 30 , 31 , 32 ]. ROS serve as key modulators of seed aging, initiating early bursts during accelerated aging, potentially leading to dynamic changes in mitochondria and seed inactivation [ 8 , 33 ].…”
Section: Discussionmentioning
confidence: 99%